Drought preparedness and response - Brown, Chris; Maddaus, Lisa A. (AWWA manual, 2019)
M60 will help water managers facing water shortages by illustrating how to employ tried-and-true strategies and tactics of drought mitigation, as well as introducing new tools and methods. The manual accomplishes this by providing a step-by-step process to anticipate and respond to water shortages through a structured planning process.